First confirmed presence of the Red Sea goatfish Parupeneus forsskali (Fourmanoir & Guézé, 1976) from Cyprus. Issue 1 (December 2016) - Chartosia, Niki; Michailidis, Nikolas
Abstract Background Cyprus is affected by the invasion of non-indigenous 'lessepsian' species due to its proximity to the Suez Canal. Thus, recent ongoing studies in the marine area of Cyprus reveal new records of such Erythrean species. Results The first confirmed presence of the Red Sea goatfishParupeneus forsskali in the coastal waters of Cyprus is reported. Description of the specimen, together with some distributional notes of the species in the Mediterranean are provided. Conclusions This record ofP. forsskali from Cyprus, together with the previous occurrences in Israel, Lebanon and Turkey supports further the establishment of a population in the eastern Mediterranean.